Interest for Philosophy (Journal of Parents and Teachers, 2012)
The interest for learning philosophy should start showing people what is philosophy. The different types of interest derive from what philosophy is and what tries to be. For this, in this article, there are some aspects and matters explained: the philosohpy as a way of admiration and metaphysics, as a way of open yourself to a self experience and to transcendency after limit situations, as a way of life that joins knowledge and kidness and, also, as a way of asking not the means bu the purposes and the search of meaning.
Keywords: The interest for learning philosophy should start showing people what is philosophy. The different types of interest derive from what philosophy is and what tries to be. For this; in this article; there are some aspects and matters explained; the philosoh